A Broadband X-Ray View of the Precessing Accretion Disk and Pre-eclipse Dip in the Pulsar Her X-1 with NuSTAR and XMM-Newton - Brumback, Mckinley C.; Hickox, Ryan C.; Furst, Felix S.; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn; Staubert, Ruediger; Vrtilek, Saeqa (Astrophysical Journal, 2021)
We present a broadband X-ray timing study of the variations in pulse behavior with the superorbital cycle in the low-mass X-ray binary Her X-1. This source shows a 35 day superorbital modulation in X-ray flux that is likely caused by occultation by a warped, precessing accretion disk. Our data set consists of four joint XMM-Newton and NuSTAR observations of Her X-1 which sample a complete superorbital cycle. We focus our analysis on the first and fourth observations, which occur during the bright "main-on" phase, because these observations have strongly detected pulsations. We added an archival XMM-Newton observation during the "short-on" phase of the superorbital cycle because our observations at that phase are lower in signal to noise. We find that the energy-resolved pulse profiles show the same shape at similar superorbital phases, and the profiles are consistent with expectations from a precessing disk. We demonstrate that a simple precessing accretion disk model is sufficient to reproduce the observed pulse profiles. The results of this model suggest that the similarities in the observed pulse profiles are due to reprocessing by a precessing disk that has returned to its original precession phase. We determine that the broadband spectrum is well fit by an absorbed power law with a soft blackbody component and show that the spectral continuum also exhibits a dependence on the superorbital cycle. We also present a brief analysis of the energy-resolved light curves of a pre-eclipse dip, which shows soft X-ray absorption and hard X-ray variability during the dip.
CRIS-Team WoS Importer:2021-12-10